Teologi Keramahan Allah: Sebuah Pembacaan Kristologi Lukas - Manurung, Frans Setyadi (Faculty of Theology Duta Wacana Christian University, 2018)
Abstract This paper is an attempt to present a hospitable christology model that is relevant for answering issues of plurality in the Indonesian context. The author raises one of the problems of christology, namely the controversy over the idea of Jesus’ subordination to and belief in God in both Luke’s writings. Developing the synthesis approach of Douglas H. Buckwalter, it is suggested that Luke’s Christology is traditional and does not show any conflict with these two ideas. Luke’s ability to build a synthesis in his Christology is precisely an important point for Luke in depiciting Jesus as a manifestation of God’s hospitality and a model for his community. Luke’s Christology that presents the idea of the hospitality of God, is an important contribution for the construction of a model of Christian life in the Indonesian context. AbstrakTulisan ini adalah usaha untuk menampilkan sebuah model kristologi yang penuh dengan keramahan, yang dapat dihidupi dan menjadi kontribusi dalam menjawab persoalan-persoalan pluralitas yang ada di Indonesia. Penulis mengangkat salah satu persoalan kristologi—yang juga menjadi persoalan klasik dalam perdebatan kristologi—yaitu perdebatan yang berhubungan dengan gagasan subordinasi Yesus dan keyakinan Yesus sebagai Tuhan dalam kedua tulisan Lukas. Sehubungan dengan masalah tersebut, penulis mengembangkan pendekatan sintesis yang telah dilakukan Douglas H. Buckwalter dalam bukunya The Character and Purpose of Luke’s Christology untuk menunjukkan bahwa Kristologi Lukas bersifat tradisional dan sama sekali tidak menunjukkan adanya persoalan dengan kedua gagasan tersebut. Kemampuan Lukas untuk membangun sintesa dalam Kristologinya, justru menjadi poin penting bagi Lukas untuk menjadikan Yesus sebagai wujud keramahan Allah dan menjadi model bagi komunitasnya. Kristologi Lukas yang menghadirkan gagasan keramahan Allah, adalah kontribusi penting untuk membangun model kehidupan kekristenan dalam konteks Indonesia.